Urban Agriculture in Public Space Planning and Designing for Human Flourishing in Northern European Cities and Beyond - Sirowy, Beata; Ruggeri, Deni.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
This open access book discusses urban agriculture initiatives integrated in public space of dense inner-city neighbourhoods, thereby ensuring its accessibility for large and diverse segments of urban populations. It specifically focuses on the potential impacts of urban agriculture on human well-being (both on individual and community levels), and how planning, design, policy and management practices can maximize these impacts. The book addresses urban agriculture on both a micro and macro scale to facilitate a transition to more sustainable lifestyles and enhance the quality of urban life. It also discusses ways to permanently integrate urban agriculture in existing and planned public spaces in a visually attractive, socially inclusive, and democratic manner to claim and reclaim the right to the city. Based on the research outcomes of the project (3z(BCultivating Public Space: urban agriculture as a basis for human flourishing and sustainability transition in Norwegian cities(3y (Bfunded by the Research Council of Norway, the book emerges from a Norwegian context, but extends to include international urban agriculture cases from the Netherlands, Denmark, the UK and more. By including a diversity of voices and cultural perspectives, the editors aimed to make this book engaging and relevant to an international audience of researchers, policy makers, urban designers, planners, educators, community activists, residents, and public space users of the sustainable, compact city of today and the future.s
Chapter 1. Setting the stage: urban agriculture and public space -- PART I: Conceptual foundations: urban agriculture for human flourishing -- Chapter 2. Capabilities and beyond: towards an operationalization of eudaimonic well-being in cities -- Chapter 3. Cultivating Virtue: neo-Aristotelian concepts in public space development -- PART II: Public urban agriculture in Northern European contexts -- Chapter 4. Cultivating publicness through urban agriculture: learning from Aarhus and Rotterdam -- Chapter 5. The rise and fall of public urban gardens: four cases from in and around Copenhagen -- 6. Practicing urban agriculture in public space: experiences from Oslo -- Chapter 7. The importance of social programming in urban agriculture: a practitioner$1 (Bs experiences from Norway -- PART III: When education gets in the urban agriculture mix -- Chapter 8. Key characteristics of co-produced urban agriculture visions in Oslo -- Chapter 9. Urban Agriculture from prescription to adaptation in the future dense city. A view from the classroom -- Chapter 10. Urban Agriculture and the right to the city: a practitioner$1 (Bs roadmap -- PART IV: Planning for urban agriculture in Norway -- Chapter 11. Motivations for urban agriculture policies: evidence from Norway$1 (Bs largest urban areas -- Chapter 12. The development and institutionalization of urban agriculture policy: what characterizes the emerging governance models in three Norwegian cities? -- PART V: A way forward for urban agriculture in cities and communities -- Chapter 13. Raising the ambition of urban agriculture in public space: nurturing urban agroecology and more-than-human health -- Chapter 14. Final reflections: Lessons learnt, limitations, and the way forward.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Human geography; Agriculture; Quality of life; Sociology, Urban; Human Geography; Agriculture; Quality of Life Research; Urban Sociology